Respuesta :

Answer:

Step-by-step explanation:

2x - 6y =  6

-3x + 3y = 5       multiply this equation both side by 2 then add it to the first

                         equation

2[-3x + 3y]  = 2[5]       ------->     -6x    +   6y   =  10

-6x    +   6y   =  10

2x    -    6y   =  6

------------------------   add both equation

-6x + 2x + 6y - 6y  = 10 + 6

   -4x    +     0      =   16

               -4x       =    16

                       x   =  16/(-4)

                      x    =  -4      how find  y   I used the first eq, but either one works

   2x - 6y  =  6          x = -4    solve for y

2[-4]  - 6y  =  6

   -8  -  6y  = 6          add 8 to both sides

    -8 + 8 - 6y = 6 + 8

             -6y   =  14

                y    =  14/(-6)

                y     =  -7/3

ACCESS MORE